2009
DOI: 10.1111/j.1365-2842.2009.01944.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the instrumental assessment of implant stability in dry human mandibles

Abstract: The aim of this study was to determine the intra- and interobserver reliability and validity of the instrumental assessment of primary dental implant stability, using resonance frequency analysis (RFA). Sixteen tapered implants and 16 cylindrical implants were installed in eight unfixed dry human mandibles (Cawood classification IV/V). Implant stability quotients (ISQ; the outcome variable of RFA) and peak removal torque were determined. Both the intra-observer reliability and the interobserver reliability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 27 publications
3
29
0
1
Order By: Relevance
“…This analysis, presented as an implant stability quotient (ISQ, with a value between 0 and 100), in which a higher value indicates increased stability 2,6,13 ; is influenced by the bone adjacent to the implant and the rigidity of the bone-implant interface [2][3][4]9,13 . This statement corroborates this study's results, in which higher resonance frequency values were found in implants inserted in wood and 40 PCF Nacional ® polyurethane, the materials with the greatest rigidity amongst those chosen as bone substitutes; it also corroborates studies that show that the resonance frequency of implants is proportional to the rigidity of the surrounding material.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This analysis, presented as an implant stability quotient (ISQ, with a value between 0 and 100), in which a higher value indicates increased stability 2,6,13 ; is influenced by the bone adjacent to the implant and the rigidity of the bone-implant interface [2][3][4]9,13 . This statement corroborates this study's results, in which higher resonance frequency values were found in implants inserted in wood and 40 PCF Nacional ® polyurethane, the materials with the greatest rigidity amongst those chosen as bone substitutes; it also corroborates studies that show that the resonance frequency of implants is proportional to the rigidity of the surrounding material.…”
Section: Discussionmentioning
confidence: 99%
“…The Periotest is an instrument that assesses tooth or implant mobility 8 , however its applicability for this purpose is poor due to its low senitivity 2,4,8 . Insertion torque is equal to the implant's final seating torque in the receiving bone site 6 , but this can only be assessed per operandum 2,8 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations